The adaptation of Venezuelan migrants from an educational perspective in Peru and Ecuador - Yoya Flores-Pérez; Olga Mendoza-León; Luz Cruzado Saucedo; Juan Carlos Rodríguez-Soto (International Journal of Evaluation and Research in Education (IJERE), 2025)
Migration processes in the world promote socio-cultural, environmental and economic changes. The migrant population commonly suffers from discrimination, xenophobia, and labor abuse, with the educational level being a very important incentive for the adequate adaptation of the migrant. Peru and Ecuador host close to two million migrants; therefore, we sought to identify the educational level, living conditions, environmental care, and labor conditions of the migrant population and the level of association between them. For this purpose, a descriptive, non-experimental, cross-sectional study was carried out using a 24-question questionnaire to 120 migrants over 18 years of age who voluntarily participated in the study. The results showed that 50% had a fair level of education, 35% had a poor level, and only 15% had a good level. A total of 56.67% had a poor standard of living, 33.33% a fair standard of living, and 10% a good standard of living. There were 96.67% reported a good level of care for the environment. The 57.5% have poor working conditions; 40.83% regular, and 1.67% good. The study concludes that a good educational level allows a better adaptation process; likewise, educational level was significantly associated with living and working conditions.